Trade, Education, and Income Inequality - Markus Brueckner; Ngo Van Long; Joaquin Vespignani (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines the relationship between countries' bilateral trade with the United States that is not due to gravity (non-gravity trade) and the distribution of income within countries. In countries where only a small share of the population are educated, an increase in non-gravity trade is associated with a significant increase in income inequality. As education of the population increases the correlation between non-gravity trade and income inequality becomes smaller. Non-gravity trade has no significant effect on income inequality in countries that are world leaders in education.
Keywords: F10; E20; 330; non-gravity trade; inequality; education